ECONOMIC AND BIOLOGICAL EVALUATION OF TOMATO HYBRIDS IN FILM GREENHOUSES OF THE MOUNTAIN CRIMEA - Максудовой, М.; Бобось, И. (SWorldJournal, 2021)
It is possible to expand the supply of high-quality various tomato products for consumers to the fresh market in the foothills of Crimea through the use of unheated film greenhouses, where you can regulate the microclimate and ensure optimal growth and d